The Influence of Entrepreneurship Development Policies and Strategies Regarding Micro Wakaf Bank (BWM) And Its Implications for Community Economic Empowerment in The Boarding School of Cirebon - Udin Komarudin; Ah Fathonih; Nurrohman Nurrohman (International Journal of Economics, Management and Accounting (IJEMA), 2024)
Micro Waqf Bank (BWM) is a very important part of community economic empowerment, especially in the Cirebon Islamic boarding school environment. This is of course in line with the government program which seeks to improve the welfare of the community by realizing economic activities with the help of business capital which does not burden business actors in returning the capital. The method used is descriptive research which aims to describe in detail the phenomena observed using regression analysis parameters. The number of samples used in this research was 92 respondents. Sampling used a documentation questionnaire. The results of this research show that government policy (X1) has a positive and significant effect on the Micro Waqf Bank (Y) with t calculated ariable policy (X1) = 1.776. The government's strategy (X2) has a positive and significant effect on the Micro Waqf Bank (Y) with t calculated ariable strategy (X2) = 1.757. Entrepreneurial development (X3) has a positive and significant effect on Micro Waqf Bank (Y) with t aritable variable for entrepreneurial development (X3) = 1.667. Micro Waqf Bank (Y) has a positive and significant effect on community economic empowerment (Z) with t calculated for Micro Waqf Bank (Y) = 1.871. The community's shift from initially relying on loans from loan sharks to participating in Micro Waqf Bank (BWM) financing is expected to be part of a concrete step towards realizing the aim of establishing the Micro Waqf Bank (BWM), namely to realize community welfare.